Penal Policy to Children As Recidivists Reviewed From Law No. 35/2014 On Child Protection : A Study On Surakarta District Court Ruling No.02/Pid.Sus.Anak/2014/PN.Skt. - Erwin Pangihutan Situmeang; Madiasa Ablisar; Mahmud Mulyadi; Edy Ikhsan (USU LAW JOURNAL, 2019)
Abstract. Penal system for children today still does not provide justice for them. It is grounded on the Penal Code, Law Number 11/2012 on Child Criminal Justice System (hereinforth is referred to as UU SPA), and Law Number 35/2014 on child protection which implementation is not yet maximum to secure children’s rights and future as either the perpetrators or victims.. The policy to children to prevent recidivists is made by 2 (two) ways; namely penal policy and non-penal policy. Penal policy is the policy made based on best legal formulation for children, either from the Law maker, law enforcer, or law abiding society. Non-penal policy that is more preventive to social effects and imprisonment, is the last effort for children as recidivists. The ruling Number 02/PID.Sus.Anak/2014/PN.Skt which punishes the child with the weighting for being a recidivist needs to be reviewed. UU SPA and Law on Child Protection need to revise the punishment for children to be more treating, not torturing. Punishment for children should be made based on double track system stating that imprisonment and treatment sanctions have to be balanced.   Keywords: judge’s ruling, children as recidivists, child protection